LEGO super nature - Skene, Rona; Briscoe, Jason; Dias, Nate; Ombler, Gary (New York : DK Publishing, 2021)
Did you know there's a plant that eats insects? And a mammal that can fly? LEGO Super Nature includes fascinating facts from the natural world, all illustrated with LEGO builds.
Water and ice -- Forests -- Mountains and lowlands.
Includes index.
110234
Keywords: LEGO toys -- Juvenile literature; Models and modelmaking; Educational toys; Nature; Animals; Informational works; Illustrated works; Juvenile works